Assessment of Stx-1A gene polymorphism (rs1569061) in relation to the development of multiple sclerosis in Egyptian patients - Habib, Christine A; El-Sebai, Aziza A; Fouad, Mohamed M; El-Mohamdy, Marwa A; Abdel Ghani, Amani M; Bawady, Somia A (The Egyptian journal of immunology, 2024)
Multiple sclerosis (MS) is a multifactorial polygenic disease; results from autoimmune and neurodegenerative processes which lead to multifocal lesions of the central nervous system. Axonal degeneration was found to be prominent in the inflammation period of MS and contribute to the progression of disability. Soluble N-ethylmaleimide sensitive factor attachment receptor (SNARE) complex plays a vital role in the release of neurotransmitter by synaptic vesicle fusion. Stx-1A protein (Stx-1A), a major component of the SNARE complex, is widely expressed in brain tissue. This study intended to evaluate the prevalence of the Stx-1A gene polymorphism (rs1569061) in the Egyptian population with MS and to investigate its association with various clinical factors. This study included 65 adult Egyptian MS patients and 35 age- and sex-matched normal control subjects. Diagnosis of MS was made by an experienced neurologist according to revised McDonald criteria. All Patients underwent full history taking, included Age of onset of MS, disease duration, disease course and degree of disability according to the Expanded Disability Status Scale (EDSS) and family history of neurological diseases. Stx-1A gene polymorphism (rs1569061) genotyping was performed by TaqMan assay based quantitative real time (qPCR) and verified by sanger sequencer. Genotype and allele frequencies of (rs1569061) did not differ significantly between case and control groups. No difference was detected when comparing the genotype frequency and the allele frequency to different disease parameters. Discrepancy of the minor allele frequency (MAF) of Stx-1A gene (rs1569061) between different populations was noted. In conclusion, our study in Stx-1A gene polymorphism (rs1569061) and MS showed that no difference between the patient and control as regards gene frequency and allele frequency. Predicting no association between the studied polymorphism and MS in the Egyptian population. However, discrepancy between different population was noted as regards the MAF for Stx-1A gene (rs1569061).